Application of ultrasound treatment for improving the quality of infant meat puree - Mingyang Luo (Elsevier, 2021)
Infant meat puree has an indispensable effect on the oral development and nutritional intake of infants. However, commercially available products have poor texture and relatively low digestibility. In this study, ultrasound (20 kHz and 200 W, 400 W, or 600 W) was applied to the pretreatment of raw meat for preparing infant meat puree for 15 min, 30 min, and 45 min. To assess the impact of ultrasound on infant meat puree, the viscosity, texture, water distribution, particle size and in vitro digestibility were determined. The results showed that, compared with control, viscosity and hardness of meat puree decreased and the texture was better in 400 W and 600 W groups. The content of immobilized water increased in comparison with the control. Ultrasound had no obvious effect on the digestibility of meat puree in gastric phase, but it increased the digestibility in intestinal phase with the highest digestibility (80.85%±3.33) in 600 W, 15 min group. Overall, the ultrasound parameters of 600 W for 15 min can be selected as the best condition to process infant meat puree. The findings provide a new perspective for the improvement of infant meat puree.